Epidemiological and clinical aspects of respiratory pathologies during pregnancy and puerperality - Didier, Kouamé Arthur; Alice, Diomandé Fatoumata; Charles, Kakou; Christian, Alla; Victor, Koffi Soh; Alexandre, Boko; Firmin, Kouakou (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The purpose of this study was to describe the characteristics of respiratory pathologies during pregnancy and postpartum. Methods: This was a case-control study over a 7-year period from January 2008 to December 2014 at CHU de COCODY. We compiled 86 cases of the PPH department hospitalized patients for pulmonary disease during pregnancy and for postpartum up to 42 days after delivery. The control samples were represented by those hospitalized in Obstetrics for a non-respiratory general condition during the same gravido puerperal period. Results: The age group of 20-29 years was the most affected in both groups with extremes ranging from 16 to 40 years (p=0.827). Respiratory pathology was common among housewives or unemployed women (p=0,001). Pauciparous and multiparous were the most affected (p=0.020). They had a medical history in 55.8% of cases versus 22.8% in controls (p=0.001). Positive HIV serology was also found (p=0.001) and was most often passive tobacco related (p=0.015). Respiratory pathology was progressive in 72.9% in cases vs 8.9% (p=0.001) with dyspnoea as the main sign (58%). Tuberculosis (29.70%) was the most common respiratory disease. Maternal complications accounted for 48.1% of PPH vs 25.6% (p=0.001) with maternal mortality of 11.6% (p = 0.001). As for foetal prognosis, 25.6% of foetal complications were noted in patients admitted to PPH versus 48.1% (p = 0.001). Conclusions: Respiratory disease during the gravido puerperal period is severe with significant maternal repercussion.